PELUANG DAN TANTANGAN PELAKSANAAN PIDANA ISLAM DI INDONESIA - Massadi Massadi (Al-Bayyinah, 2019)
AbstractThis study discusses the opportunities and challenges of the implementation of Islamic criminal law in Indonesia, which parenthetically is the rule of law. This study examines the opportunities and challenges of applying criminal law in Indonesia. The portrait of Islamic criminal law that is understood by some people is cruel and inhuman, even though such an impression arises because it is not seen as a whole. Islamic criminal law which is part of Islamic law, for example the law of cutting off the hands is often accused of being too cruel and unfair. Though this punishment was only handed down when a number of strict requirements were met. Islamic criminal law has the opportunity to be applied when the principle of law enforcement has a deterrent effect. However, if law enforcement is seen as merely pragmatic and a place to dictate something that is unclear, then Islamic criminal law cannot be applied.Keywords: Opportunity, Challenges, Islamic Criminal Law.AbstrakKajian ini membahas peluang dan tantangan pelaksanaan pidana Islam di Indonesia yang notabenenya adalah Negara hukum. Kajian ini menelaah peluang dan tantangan penerapan hukum pidana di Indonesia. Potret hukum pidana Islam yang dipahami sebagian orang adalah kejam dan tidak manusiawi, padahal kesan semacam itu muncul karena tidak melihat secara utuh dan menyeluruh. Hukum pidana Islam yang merupakan bagian dari syariat Islam, misalnya hukum potong tangan sering dituding terlampau kejam dan tidak adil. Padahal hukuman ini baru dijatuhkan ketika sejumlah persyaratan yang ketat terpenuhi. Hukum pidana Islam mempunyai peluang untuk diterapkan bilamana prinsip penegakan hukum memberikan efek jerah. Namun bila penegakan hukum dipandang sebagai pragmatis semata dan ajang untuk mendialokkan sesuatu yang tidak jelas hukumnya, maka hukum pidana Islam tidak mampu diterapkan.Kata Kunci: Peluang, Tantangan, Pidana Islam.